Evaluation of public awareness and performance toward the safe use of household disinfectants-cleaners to prevent COVID-19 in the Emirate of Abu Dhabi - Nisreen Alwan; Shatha Almazrouei; Mariam Almazrouei; Jawaher Aldhaheri; Fahad Alismaili; Wissam Ghach (Frontiers in Public Health, 2023)
IntroductionDisinfection is one of the most effective hygienic practices that would limit the spread of the Coronavirus Disease (COVID-19) through deactivating the coronavirus on contaminated skin, supplies, and surfaces. However, the type and concentration of disinfectants should be carefully selected to avoid damaging surfaces and to limit the side effects of these chemicals on household members and users. The aim of this study is to assess the public levels of awareness and performance concerning the safe use of household cleaning products and disinfectants during the spread of COVID-19 in the Emirate of Abu Dhabi.MethodsThe cross-sectional study was conducted between October and December 2021 among 750 residents of Abu Dhabi, Al Dhafrah, and Al-Ain regions. A google survey was distributed electronically for the online recruitment of the general population. Mann-Whitney and Kruskal-Wallis tests were used to determine whether significant differences exist in the levels of awareness and performance with regard to gender, region, education level, and diagnosis with COVID-19. Spearman correlation was used to test if any correlation existed between levels of awareness and performance. Kruskal-Wallis test was also used to check if significant differences exist in the mean score of performance with respect to irritation-to-poisoning symptoms.ResultsThe study population recorded a lower mean score of awareness (5.37 out of 12) than performance (11.75 out of 16). The majority of the study population claimed a minimum of one irritation-to-poisoning symptom during the handling of household cleaners and disinfectants. Significant differences exist in the awareness and performance mean scores among various educational levels (P < 0.001). The level of awareness was statistically significant with regard to infection with SARS-CoV-2 (P < 0.05). Also, the level of performance was significantly different between males and females (P < 0.001). Kruskal-Wallis test showed that the mean score of performance is statistically significant with all the studied irritation-to poisoning symptoms (P < 0.05).ConclusionsAwareness campaigns and training programs are recommended to address the safe use of household cleaning products and disinfectants in the United Arab Emirates (UAE).